Ask me, listen to me, treat me well and I shall tell: a qualitative study of Swedish youths' experiences of systematic assessment of sexual health and risk-taking (SEXIT). Issue 1 (31st December 2022) - Hammarström, Sofia; Bernhardsson, Susanne; Nilsen, Per; Elisson, Jennie; Frostholm, Ellinor; Lindroth, Malin
Abstract: Sexual ill health among young people, in terms of sexually transmitted infections (STIs), unintended pregnancy, transactional sex and sexual violence, is a global public health concern. To that end, the SEXual health Identification Tool (SEXIT) was developed. The purpose of this study was to explore the visitors' experiences of a youth clinic visit when SEXIT was used. A purposively selected sample of 20 participants (16–24 years of age) was recruited from three Swedish youth clinics using SEXIT. Participants were interviewed individually in March and April 2016, and data were analysed using inductive qualitative content analysis. The analysis resulted in four main categories describing the participants' experiences of using SEXIT: "Issues of concern" includes descriptions of the items in SEXIT as important; "Enabling disclosure" describes how SEXIT serves as an invitation to talk and facilitates disclosure of negative experiences; "Road to change" captures experiences of the conversation with the healthcare professional; and "Managing power imbalance" describes experiences regarding the response and attitudes of the healthcare professional as well as the participants' fears of being judged. The categories are connected by the overarching theme "Ask me, listen to me, treat me well and I shall tell". This study contributes knowledge on young people's experiences of a tool-supported dialogue on sexual health and risk-taking initiated by the healthcare professional. Structured questions in a written format, as a basis for dialogue, are appreciated and experienced as a functioning way of addressing sexual ill health and risk-taking at Swedish youth clinics.